Real-World Management and Clinical Outcomes of Stroke Survivors With Atrial Fibrillation: A Population-Based Cohort in Spain - Clara L. Rodríguez-Bernal; Clara L. Rodríguez-Bernal; Francisco Sanchez-Saez; Francisco Sanchez-Saez; Daniel Bejarano-Quisoboni; Judit Riera-Arnau; Gabriel Sanfélix-Gimeno; Gabriel Sanfélix-Gimeno; Isabel Hurtado; Isabel Hurtado (Frontiers Media S.A., 2021)
Objective: Despite the continuous update of clinical guidelines, little is known about the real-world management of patients with atrial fibrillation (AF) who survived a stroke. We aimed to assess patterns of therapeutic management of stroke survivors with AF and clinical outcomes using data from routine practice in a large population-based cohort.Methods: A population-based retrospective cohort study of all patients with AF who survived a stroke, from January 2010 to December 2017 in the Valencia region, Spain (n = 10,986), was carried out. Treatment strategies and mean time to treatment initiation are described. Temporal trends are shown by the management pattern during the study period. Factors associated with each pattern (including no treatment) vs. oral anticoagulant (OAC) treatment were identified using logistic multivariate regression models. Incidence rates of clinical outcomes (mortality, stroke/TIA, GI bleeding, and ACS) were also estimated by the management pattern.Results: Among stroke survivors with AF, 6% were non-treated, 23% were prescribed antiplatelets (APT), 54% were prescribed OAC, and 17% received OAC + APT at discharge. Time to treatment was 8.0 days (CI 7.6-8.4) for APT, 9.86 (CI 9.52-10.19) for OAC, and 16.47 (CI 15.86-17.09) for OAC + APT. Regarding temporal trends, management with OAC increased by 20%, with a decrease of 50% for APT during the study period. No treatment and OAC + APT remained relatively stable. The strongest predictor of no treatment and APT treatment was having the same management strategy pre-stroke. Those treated with APT had the highest rates of GI bleeding and recurrent stroke/TIA, and untreated patients showed the highest rates of mortality.Conclusion: In this large population-based cohort using real-world data, nearly 30% of AF patients who suffered a stroke were untreated or treated with APT, which overall is not recommended. Treatment was started within 2 weeks as recommended, except for OAC + APT, which was started later. The strong association of APT treatment or non-treatment with the same treatment strategy before stroke occurrence suggests a strong therapeutic inertia and opposes recommendations. Patients under these two strategies had the highest rates of adverse outcomes. An inadequate prescription poses a great risk on patients with AF and stroke; thus monitoring their management is necessary and should be setting-specific.